TAGX (Safety Distancing Tagging for Table) / Anes Aqilah Abdul Aziz and Norarifah Ali - Abdul Aziz, Anes Aqilah; Ali, Norarifah (Faculty of Art and Design, 2021)
A year ago we were shocked by a pandemic that was first found in Wuhan, China but now has spread widely in our country since 24th January 2020. It is called Coronavirus Disease 2019 or COVID-19. This matter not only threatens our health but the income and livelihood of our society is also affected. However, the public must still follow or comply with the conditions set under the Recovery Movement Control Order (RMCO). The Health director-general Tan Sri Dr Noor Hisham Abdullah has said by practicing social distancing in public places and complying with the Standard Operating Procedure (SOP) prevent the spread of the COVID-19 pandemic. One of the examples of SOP in public places is physical distancing based on the table size. Therefore, each premise makes a tagging on the tables or any places that are not allowed to be occupied. Among the initiatives that have been used are paper, tape and mannequin. However, there are still some in our society who do not comply with the rules and take this matter lightly. Another reason for them to not follow the tagging given is because the material used is easily damaged by the user.